PREDICTION OF THE INCIDENCE OF PROSTATE CANCER IN THE URAL ECONOMIC REGION OF THE RUSSIAN FEDERATION - K. A. Ilyin; A. V. Zamyatin; G. P. Bystray; S. A. Okhotnikov (Исследования и практика в медицине)
Objective. To quantify and to forecast the dynamics of registered cases of prostate cancer (PC) in the Ural economic region.Material and methods. The study used official statistics on the incidence of prostate cancer in the Russian Federation for the period since 2004 to 2013. inclusive. For the predictive calculation we used the upgraded Hurst method, wich is also called the method of normalized range (R/S). All calculations and the resulting graphs are made with specialized software.Results. Based on available statistic data for a specified period of time, we constructed the graphs of the figure of registered cases of prostate cancer for each subject the Ural economic region and for Russia as a whole. After 2013. graphics were built on the basis of the calculated forecast data. The forecast was built with the assumption of constant further factors contributing to identifying patients with prostate cancer in the study area. The results indicate the inhomogeneous statistics of the indicator for the study area is subject to subjective economic division. Overall, on the territory of the Ural economic region the increase of the incidence of prostate cancer is expected. The incidence rate in Russia is characterized by stable growth, which is expected in the future (a projection until 2018).Conclusions. In recent years, the development of medical technology has led to the expansion of the arsenal of diagnostic and therapeutic opportunities in prostate cancer leading to the emergence of alternative choice of activities in the preparation of individual treatment plan of the patient with newly diagnosed. The increase in the share of the costs in this section of Oncology is due both to the increase in the absolute number of detected cases of the disease, and with changes in the quality of aid. In this regard, the observed and projected increase in the recorded incidence of prostate cancer naturally raises the question of the continued availability of quality medical care in this type of pathology. Planning and controlling costs for aid should be based on the received data about the forecast of the incidence of prostate cancer.